The situation of unaccompanied minors in Romania in the course of Europe's refugee crisis - Raluca Bejan; Andreea Iorga Curpan; Olga Amza (Social Work & Society, 2017)
This paper discusses the legal-juridical framework that outlines the situation of unaccompanied refugee minors (UAM) in Romania. It reports on the numbers of underage migrant children in Romania, it examines some of the official ways of entry and claiming asylum, and it insists on the social policy responses formulated for this population, particularly within the context of the growing influx of refugees' entries in Europe. It provides recommendations for social work practice and discusses social work implications on the matter.